The effect of UPMB10 and Pseudomonas spp. on paddy growth in different density - Suwardi, Abdullah (2014)
Oryza sativa or rice plant is a type of cereal crops and one of the most popular crops in worldwide. Malaysia with a population of 28 million people is not able to supply sufficient amount of rice and had to import it. This is due to the less area of cultivation. In production systems, farmers are using chemical fertilizer as the method to increase the plant growth. In long time effect, this method can affect to soil fertility, environment and to human beings. One of the cultivation techniques in increasing rice plant growth and yield are by implying several ways in maximising use of land and in the same time, it will contribute to sustainable agriculture. The objectives for this study are to determine the effect of the planting density and plant growth promoting rhizobacteria (PGPR) to increase rice plant growth. The project was carried out in a glasshouse using polybag with different seedling numbers (1 seedling per hill, 2 seedlings per hill and 3 seedlings per hill) and 5 ml (1x108 CFU/ml ) different PGPR per plant (UPMB10, Pseudomonas spp. and UPMB10 mix with Pseudomonas spp.) will be inoculated into the soil three days and 31 days after transplanting (DAT). Each treatment with five replications will be arranged in Randomized Complete Block Design (RCBD) and data collected analysis with Analysis of Variance (ANOVA). The effect of the planting density and PGPR can be seen through a number of tiller, plant height, dry weight, root morphology and contain of nutrient after 45 days.